2020
DOI: 10.1007/s00345-020-03091-5
|View full text |Cite
|
Sign up to set email alerts
|

How much energy do we need to ablate 1 mm3 of stone during Ho:YAG laser lithotripsy? An in vitro study

Abstract: Introduction Holmium:yttrium-aluminium-garnet (Ho:YAG) is currently the gold standard for lithotripsy for the treatment of all known urinary stone types. Stone composition and volume are major determinants of the lithotripsy. This in vitro study evaluated the required energy to ablate 1 mm 3 of various stone types with different laser settings using Ho:YAG. Methods 272 µm core-diameter laser fibers (Boston Scientific © ) were connected to a 30 Watt MH1 Ho:YAG generator (Rocamed®). An experimental setup consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“… 6 While holmium laser is the gold standard of laser lithotripsy, controversy still exists on the optimal laser energy and settings, and uncertainty around the power needed to ablate a specific size and composition of stones. 7 Hence, there is a heated debate to determine whether a low- or high-power laser system is better.…”
Section: Introductionmentioning
confidence: 99%
“… 6 While holmium laser is the gold standard of laser lithotripsy, controversy still exists on the optimal laser energy and settings, and uncertainty around the power needed to ablate a specific size and composition of stones. 7 Hence, there is a heated debate to determine whether a low- or high-power laser system is better.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated operative time, catheterization, hospital stay, stone-free rates, and complication rates of group A and Group B are mentioned in Table 2. The Ho: YAG laser fragment the stones in minute dusting constituent parts, trouble-free to pass lacking soreness or other undesirable results 12,13 . Our study outcomes demonstrated the elevated frequency of female patients with 60% and 63.3% in the laser versus pneumatic group.…”
Section: Resultsmentioning
confidence: 99%
“…We could have also used the characteristics of the ablated crater: deepness, width, length and produced fragments’ size. Consequently, even if our method has been validated by previous in vitro and in vivo studies, we could have analyzed the stone samples using a profilometric method [ 4 , 7 , 9 , 15 , 24 ]. A further dedicated experiment should directly compare both profilometric and three-dimensional segmentation methods.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the ablation volumes, a three-dimensional scanning (micro-CT Quantum FX, Perkin Elmer © , Waltham, MA, USA) of the artificial stones and subsequent 3D segmentation using 3DSlicer software (NIH © ) was used ( Figure 2 ) [ 4 , 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%